2021
DOI: 10.1101/2021.02.12.21249710
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk of Corona virus disease 2019 (COVID-19) among spectacles wearing population of Northern India

Abstract: Introduction- Severe Acute Respiratory Syndrome Corona virus-2 (SARS-CoV-2) spread mainly through respiratory droplets and contact routes. Long term use of spectacles may prevent repeated touching and rubbing of the eyes. Aim of the study is to compare the risk of COVID-19 in long term spectacles wearers with the risk in persons not using spectacles. Objectives- To know the association between infection with SARSCoV-2 and wearing of spectacles. Materials and methods- In this study, 304 patients of Corona virus… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…We also found three prevalence studies that looked at potential protective effect of regular eyewear in general population [15][16][17] . They suggested that wearing regular eyewear for more than 8 hours a day could reduce SARS-CoV-2 infection, but there was insu cient data to establish causation.…”
Section: Resultsmentioning
confidence: 99%
“…We also found three prevalence studies that looked at potential protective effect of regular eyewear in general population [15][16][17] . They suggested that wearing regular eyewear for more than 8 hours a day could reduce SARS-CoV-2 infection, but there was insu cient data to establish causation.…”
Section: Resultsmentioning
confidence: 99%
“…We also found three prevalence studies that looked at potential protective effect of regular eyewear in general population [15][16][17] . They suggested that wearing regular eyewear for more than 8 hours a day could reduce SARS-CoV-2 infection, but there was insufficient data to establish causation.…”
Section: Figure 1 Screening and Selection Of Articlesmentioning
confidence: 99%